Public Scholarship in Literary Studies - Arteaga, Rachel (Amherst College Press, 2021)
Public Scholarship in Literary Studies demonstrates that literary criticism has the potential not only to explain, but to actively change our terms of engagement with current realities. Rachel Arteaga and Rosemary Johnsen bring together accomplished public scholars who make significant contributions to literary scholarship, teaching, and the public good. The volume begins with essays by scholars who write regularly for large public audiences in primarily digital venues, then moves to accounts of research-based teaching and engagement in public contexts, and finally turns to important new models for cross-institutional partnerships and campus-community engagement. Grounded in scholarship and written in an accessible style, Public Scholarship in Literary Studies will appeal to scholars in and outside the academy, students, and those interested in the public humanities.